Using Environmental Learning Models to Increase the Students’ Productive Skills - Siti Oriza Salsijanti; Suyadi; Esti Junining; Wike (Future Science)
It is found that most of the students in Senior high school do not have adequate awareness of the environment and also find writing difficult. They are also not able to properly communicate in English. To overcome these problems, some learning models were used to teach environmental education as a tool to construct their knowledge. The study investigated the integrating environmental education into the PBL and PjBL methods in learning English. Quasi-experimental design, non-randomized control group, and pretest- posttest were used in the study. The subjects of the study were taken from the population of the XI grade students of SMAN 1 Gambiran, Banyuwangi, Indonesia in 2018/2019. The result of the Mann-Whitney U-Test can be shown that students taught using PBL and PjBL through scaffolds and a campaign achieve significantly higher scores in writing and speaking compared to those taught using the conventional method.